2006
DOI: 10.1002/pip.692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of solar energy potential and PV module performance in the Gobi Desert of Mongolia

Abstract: Here, we present the results of evaluation of solar energy potential and photovoltaic (PV) module performance from actual data measured over a period of more than 2 years in the Gobi Desert of Mongolia. To allow estimation of solar energy potentials and durability of PV systems in the Gobi Desert area, a data acquisition system, including crystalline silicon (c-Si), polycrystalline silicon (p-Si) modules, and two sets of precision pyranometers, thermometers, and anemometer, was installed at Sainshand City in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…The Research Center for Photovoltaics (RCPV), National Institute of Advanced Industrial Science and Technology (AIST) has performed outdoor performance measurements of various kinds of PV modules at different locations in Asia as shown in Figure 1: Sainshand, Mongolia in collaboration with National University of Mongolia (NUM) and National Renewable Energy Center of Mongolia (NREC) since October 2002 10, AIST Tsukuba in Japan since July 2004, Bangkok, Thailand in collaboration with National Science and Technology Development Agency (NSTDA) since January 2006 11, New Delhi, India in collaboration with Solar Energy Centre (SEC) and National Physical Laboratories (NPL) since January 2009, and AIST Kyushu in Japan since February 2009. In particular, the outdoor measurements at AIST Kyushu are planning to be extended up to a total of 100 kW composed of both PV modules and PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…The Research Center for Photovoltaics (RCPV), National Institute of Advanced Industrial Science and Technology (AIST) has performed outdoor performance measurements of various kinds of PV modules at different locations in Asia as shown in Figure 1: Sainshand, Mongolia in collaboration with National University of Mongolia (NUM) and National Renewable Energy Center of Mongolia (NREC) since October 2002 10, AIST Tsukuba in Japan since July 2004, Bangkok, Thailand in collaboration with National Science and Technology Development Agency (NSTDA) since January 2006 11, New Delhi, India in collaboration with Solar Energy Centre (SEC) and National Physical Laboratories (NPL) since January 2009, and AIST Kyushu in Japan since February 2009. In particular, the outdoor measurements at AIST Kyushu are planning to be extended up to a total of 100 kW composed of both PV modules and PV systems.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The converted heat overheats Nomenclature: A, = total area of photovoltaic (PV) solar cell (m 2 ); C p , = specific heat (J kg −1 K −1 ); E p , = module's electrical power (W); E in , = received energy by solar cell (W); E t , = thermal energy in the system (W); E l , = lost energy from glass layer to ambient (W); G, = solar irradiance (W m −2 ); k, = thermal conductivity (W m −1 K −1 ); T amb , = ambient temperature (°C); T f , = water temperature (°C); T g , = glass temperature (°C); T he , = heat exchanger temperature (°C); T in , = inlet temperature (°C); T out , = outlet temperature (°C); T r , = reference temperature (°C); T s , = side boundary temperature (°C); T sc , = cell temperature (°C); T td , = Tedlar temperature (°C); U he , = heat loss coefficient from back surface to air (W m −2 K −1 ); U sca , = heat loss coefficient from glass to air (W m −2 K −1 ); U t , = heat transfer coefficient inside photovoltaic/thermal (PVT) surfaces (W m −2 K −1 ); V in , = input velocity of water (m s −1 ) Greek symbols: α g , = glass absorptivity; α sc , = PVT module absorptivity; τ g , = transmitivity of glass; ε g , = emissivity of glass; ρ, = density (kg m −3 ); μ sc , = thermal coefficient of cell efficiency (%/°C); η sc , = reference electrical efficiency of PV cell; η e , = PV electrical efficiency; η t , = PVT efficiency; η tot , = PVT overall efficiency the PV system and reduces its efficiency. 18,19 For Malaysia's climate condition, the performance of amorphous silicon PV cell is found better. Generally, a heat exchanger is attached to the PV Tedlar surface, and air/water is considered as cooling fluids to collect heat from this system.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the above-mentioned models require either detailed data [26,[30][31][32][33][34][35][36][37] and are complicated to use [35,36] or restricted in economic performance evaluation [17][18][19][20][21]41]. These limitations of the mentioned literature are barrier in easy manipulation of the system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ronak et al [40] observed that performance of amorphous silicon is well under Malaysia's tropical hot and humid climate. Adiyabat et al [41] showed that a PV module with a high-temperature coefficient, such as crystalline silicon, is advantageous for use in the Gobi Desert area.…”
Section: Introductionmentioning
confidence: 99%